Penyuluhan pencemaran lingkungan dan kesehatan masyarakat di Desa Bukit Pedusunan Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi, Riau - Ridwan Manda Putra; Sukendi Sukendi; Dewita Buchari; Syahril Nedi; Elizal Elizal (PELANTAR PRESS, 2021)
This community extention aimed at providing information and public awareness on the effect of environmental pollution (such as pollution of waters, soil,air and food) on local public health. As such, environmentally driven diseases could be minimized and avoided. The extention were done in desa Bukit Pedusunan, Kuantan Mudik Districtm Kuantan Singingi Regency in June-September 2021. The participants of total 35 persons, consists of local government, women group and young representative of each dusun within the village of Bukit Pedusunan. Pre-orservation were conducted to find main issue on environmental threats in the village. The extention were done through class presentation, interactive discussion and demonstration. The effectiveness of the extention were evaluated to the participants thorugh items in questionare which evaluate the change in knowledge. The level of understanding were categorize into very good, good and unsatisfied. Apparently, 28,6 % of the participants understand very good on the materials, while 45,7% categorized good and 8.6% unsatisfied. Accordingly, the extention were categorized success and showed that the knowledge of the participants increased. The impact on the implementation in the field were that of knowledge dissemination to womens group on preparation health food of fish meat base. In the future the skill were developed and become small scale household business which inturn could increase household economy.On the other hand local leader together with policy had implemented projusticia enforcement on illegal gold mining (PETI) in desa Bukit Pedusunan.In the future, it is hope that environmental condition of Danau Kebun Kopi were sustainable and could be used for tourism, water sport, fisheries and water irrigation function.